Roles of p75(NTR), long-term depression and cholinergic transmission in anxiety and acute stress coping - Martinowich, Keri (2011)
BACKGROUND: Stress is causally associated with anxiety. While the underlying cellular mechanisms are not well understood, the basal forebrain cholinergic neurons (BFCNs) have been implicated in stress response. p75(NTR) is a pan-neurotrophin receptor expressed almost exclusively in BFCNs in adult brain. The present study investigates whether and how p75(NTR), via regulation of the cholinergic system and hippocampal synaptic plasticity, influences stress-related behaviors. METHODS: We used a combination of slice electrophysiology, behavioral analyses, pharmacology, in vivo microdialysis and neuronal activity mapping to assess the role of p75(NTR) in mood and stress-related behaviors and its underlying cellular and molecular mechanisms. RESULTS: We show that acute stress enables hippocampal long-term depression (LTD) in adult wild-type mice, but not in mice lacking p75(NTR). The p75(NTR) mutant mice also exhibit two distinct behavioral impairments: baseline anxiety-like behavior and a deficit in coping with and recovering from stressful situations. Blockade of stress-enabled LTD with a GluA2-derived peptide impaired stress recovery without affecting baseline anxiety. Pharmacological manipulations of cholinergic transmission mimicked the p75(NTR) perturbation in both baseline anxiety and responses to acute stress. Finally, we show evidence of misregulated cholinergic signaling in animals with p75(NTR) deletion. CONCLUSIONS: Our results suggest that loss of p75(NTR) leads to changes in hippocampal cholinergic signaling, which may be involved in regulation of stress-enabled hippocampal LTD and in modulating behaviors related to stress and anxiety.